SUPERSYMMETRIC TRANSFORMATIONS AND HAMILTONIANS GENERATED BY THE MARCHENKO EQUATIONS - Sukumar, C (1988)
Three different isospectral Hamiltonians have been generated by eliminating the ground state of a given Hamiltonian using procedures based on the Marchenko equations for left- and right-incident waves and the standard model of supersymmetric quantum mechanics. It is shown that each of the two procedures based on the Marchenko equation is equivalent to the application of two appropriately chosen supersymmetric transformations.